Majallah Al Akhwal Ash-Shakhshiyyah dan Pembaharuan Hukum Keluarga di Tunisia - Dede Ahmad Permana (Jurnal Studi Gender dan Anak, 2020)
The thesis discuss about reforming and formulating Islamic Law of personal status codes in Tunisia, and it was happened by appearing Majallah al-Akhwāl Ash-Shakhshiyyah in 1956. This activity have been done in order to do some unifications to codes of personal status and more sensitive within modernity and human needs, because the traditional formula of Islamic law is not able to response the contemporary issues. Then, the personal status codes factually trigger and appear some debate and controversial in the roundtable of Islamic scholars, because its considered as opposite within Qur’ānic verses and Ḥadīth. They are; prohibiting polygamous marriage, erasing ijbār rights, setting the age limit for getting married, making the procedures of Ṭalāq, setting codes of nafaqah (the relationship between husband and wife), making procedure of Ṭalaq Ba’in (three divorces) and setting procedure of adoption. All of issues above become the articles of Constitution in Tunisia. It must be informed that all topics are inspired and adopted from the modern Islamic scholars’ opinions such as Muhammad ‘Abduh, Ṭāhir Ḥaddād and others, in addition the secularity approach which is promoted by the president of Tunisia Ḥabib Borghuiba. Thus, it drives reforming and renewing Islamic law of personal status codes in social life of Tunisia, which is considered by the majority of Islamic Scholars as more modern and progressive in Arab world.